Penerapan Metode MOORA Dalam Pemilihan Produk Unggulan Daerah Pada Dinas Ketenagakerjaan dan Perindustrian Kota Binjai - Indah Juliana; Achmad Fauzi; Hermansyah Sembiring (LKP Unity Academy, 2022)
MOORA method is a decision support system it is one that can perform calculations on attribute criteria that help decision makers to make the right decisions. Binjai City is an area that has several superior products. These products are superior and have characteristics and uniqueness that other regions do not have as well as reliable competitiveness and provide opportunities for employment opportunities for the surrounding community. To determine whether a product is included in the superior product category, this is determined by the Binjai City Manpower and Industry Office. There are several criteria that must be met, among others, labor, investment value, production capacity, production value, and BB/BP value. In this case the Department of Manpower and Industry of Binjai City finds it difficult to determine the superior product, this is because there are many criteria that must be considered. For this reason, a decision support system is needed that can help the Binjai City Manpower and Industry Office to determine regional superior products.